Blackcurrant Variety Specific Growth and Yield Formation as a Response to Foliar Fertilizers - Sorin Vâtcă; Roxana Vidican; Ștefania Gâdea; Melinda Horvat; Anamaria Vâtcă; Valentina Ancuța Stoian; Vlad Stoian (Agronomy, 2020)
Recently, there has been a growing interest in supplementing plant nutrition with foliar fertilizers. Foliar application of nutrients is considered a promising environmentally friendly strategy for improving the yield and nutrient efficiency of crops. Little work with foliar appliances on perennial fruits bushes, blackcurrant (Ribes nigrum L.), respectively, has been reported. This study was conducted to evaluate the growth and yield response of three blackcurrant varieties to macro and micronutrients’ foliar fertilizer solutions. Principal component analysis and factors environmental fitting were performed for the global assessment of growth and increases in branches length responsible for yield production throughout the entire vegetation period and reported to the final development. The results endorsed the benefits of foliar fertilization. Each variety has a preference for a specific foliar treatment. The highest increases in branches length for Ruben variety was with Ascovigor foliar fertilizer; for Tiben with Kombimax; for Tines with Mikromix. The varieties growth dynamics due to fertilizers was best fitted to foliar Kombimax. Stable models were found to all blackcurrant varieties depending on developmental stage and foliar fertilization application. Application of foliar fertilizer is very profitable in terms of pairing each variety with optimum product, which will increase its specific yield potential.